Faktor - faktor yang Memengaruhi Kinerja Guru Yayasan Marsudirini Kota Semarang Tahun Pelajaran 2021-2022 - V.Naniek Risnawati; Anastasia Lipursari; Marius Pramana (STARKI, 2022)
Factors Affecting the Teachers’ Performance at Yayasan Marsudirini Semarang. The study aims to find out how much factors affecting the performance of the teachers at Yayasan Marsudirini in Semarang. Data was collected through observation, and as many as 101 teacher questionnaires were used to assess pedagogic, professional and personality competencies of the teachers Data was analyzed using descriptive qualitative with percentage technique. The results showed that the factors influencing the performance of the teachers of Yayasan Marsudirini Semarang in this study were the principal's managerial and teachers’ loyalty. The results of this study are 1) the principal’s managerial supports institutional activities in which more than 50% of teachers with the principal’s activities